INFLUENCE OF COAL QUALITY TO THE BOILER EFFICIENCY AND OPPOR-TUNITY FOR ITS IMPROVEMENT - Bureska, Lidija (Termotehnika, 2017)
Boiler is very important part of power plant for development of industry and production, therefore its operation need to be optimized and at the same time its efficiency. Efficiency of boiler can be determined by two methods, direct and indirect method. Mentioned two methods are providing different information. Indirect method for determination of boiler efficiency includes all heat losses in the system, while direct method did not include any heat losses. In this paper are presented changes of the boiler efficiency related with coal characteristics, determined with indirect method (according to EN 12952, part 15). Influence of different characteristics of coal such as heating value, moisture and ash content on the boiler efficiency have been evaluated. According to the results of calculations and tests, combustion coal with higher heat value, increase boiler efficiency. In the paper also is analyzed influence of the other characteristics of coal to the boiler efficiency. Comparison of the calculation results with different coal characteristics, enables proper coal selection. In order to improve boilers efficiency different opportunities have been analyzed.